Traditional Agricultural Practices and the Sex Ratio Today - Alberto Alesina; Paola Giuliano; Nathan Nunn (Institute of Labor Economics (IZA), 2018)
We study the historical origins of cross-country differences in the male-to-female sex ratio. Our analysis focuses on the use of the plough in traditional agriculture. In societies that did not use the plough, women tended to participate in agriculture as actively as men. By contrast, in societies that used the plough, men specialized in agricultural work, due to the physical strength needed to pull the plough or control the animal that pulls it. We hypothesize that this difference caused plough-using societies to value boys more than girls. Today, this belief is reflected in male-biased sex ratios, which arise due to sex-selective abortion or infanticide, or gender-differences in access to family resources, which results in higher mortality rates for girls. Testing this hypothesis, we show that descendants of societies that traditionally practiced plough agriculture today have higher average male-to-female sex ratios. We find that this effect systematically increases in magnitude and statistical significance as one looks at older cohorts. Estimates using instrumental variables confirm our findings from multivariate OLS analysis.
Keywords: J1; N00; Z1; 330; sex ratio; gender roles; cultural transmission; historical persistence